PERLINDUNGAN HUKUM TERHADAP KEARIFAN LOKAL MASYARAKAT ADAT DI KABUPATEN PELALAWAN - Maryati Bachtiar; Evi Deliana (Riau Law Journal, 2023)
AbstractThe purpose of this study was to find out the efforts made by the Government of Pelalawan Regency in maintaining the local wisdom of the Petalangan indigenous people and the obstacles faced by the government of Pelalawan Regency in maintaining the local wisdom of the Petalangan indigenous people. One of the local wisdoms in Riau Province is the local wisdom of the indigenous people of Petalangan in Pelalawan Regency which has been passed down from generation to generation, such as traditional Belian medicine, zapin dance, oral literature of the Petalang people, manumbai sialang and potang mogang. For this reason, local wisdom needs to get legal protection. This type of research is empirical research. Based on the results of the research, the efforts made by the government of Pelalawan Regency in maintaining the local wisdom of the Petalangan indigenous people are by making a Regional Regulation on indigenous peoples institutions, regularly holding local wisdom activities every year, and introducing local wisdom in Pelalawan Regency through domestic and regional events. abroad. The obstacle faced by the government of Pelalawan Regency in maintaining the local wisdom of the indigenous people of Petalangan is the erosion of local wisdom along with the development of technology which is followed by an increase in the process of adopting innovation and the diffusion of technology adoption. There is no local regulation that specifically provides protection for local wisdom in Pelalawan Regency, eliminated by style. a consumptive materialistic-hedonic life pursuing worldly pleasures, as well as the lack of funds from the Pelalawan Regency APBD in introducing local wisdom in Pelalawan Regency. AbstrakTujuan penelitian ini adalah untuk mengetahui upaya yang dilakukan oleh pemerintah Kabupaten Pelalawan dalam mempertahankan kearifan lokal masyarakat adat Petalangan dan kendala yang dihadapi oleh pemerintah Kabupaten Pelalawan dalam mempertahankan kearifan lokal masyarakat adat Petalangan. Salah satu kearifan lokal di Provinsi Riau adalah kearifan lokal masyarakat adat Petalangan di Kabupaten Pelalawan yang diwariskan secara turun-temurun, seperti pengobatan tradisional Belian, tari zapin, sastra lisan orang petalangan, manumbai sialang dan potang mogang. Untuk itu, kearifan lokal tersebut perlu mendapatkan perlindungan hukum. Jenis penelitian ini adalah penelitian empiris. Berdasarkan hasil penelitian, upaya yang dilakukan oleh Pemerintah Kabupaten Pelalawan dalam mempertahankan kearifan lokal masyarakat adat Petalangan adalah dengan membuat Peraturan Daerah (Perda) tentang kelembagaan masyarakat adat. Secara rutin setiap tahun mengadakan kegiatan kearifan lokal, serta mengenalkan kearifan lokal yang ada di Kabupaten Pelalawan melalui kegiatan dalam negeri maupun di luar negeri. Kendala yang dihadapi oleh pemerintah Kabupaten Pelalawan dalam mempertahankan kearifan lokal masyarakat adat Petalangan adalah terkikisnya kearifan lokal seiring berkembangnya teknologi yang diikuti sehingga meningkatnya proses adopsi inovasi serta difusi adopsi teknologi, belum ada perda yang secara khusus memberikan perlindungan terhadap kearifan lokal di Kabupaten Pelalawan, tereliminasi oleh gaya hidup matrealistis-hedonis yang konsumtif mengejar kesenangan duniawi semata, serta kurangnya dana APBD Kabupaten Pelalawan dalam mengenalkan kearifan lokal yang ada di Kabupaten Pelalawan.